2017
DOI: 10.1097/sla.0000000000001968
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 Fatty Acids Protect Fatty and Lean Mouse Livers After Major Hepatectomy

Abstract: Objective: The aim of this study was to assess the effect of V3 fatty acids (V3FA) on fatty and lean liver in hepatic surgery. Background: The global spread of energy-dense diets has led to an endemic rise in fatty liver disease and obesity. Besides metabolic pathologies, steatosis enhances hepatic sensitivity to ischemia reperfusion (I/R) and impedes liver regeneration (LR). Steatosis limits the application of liver surgery, still the main curative option for liver cancer. V3FA are known to reverse steatosis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 44 publications
3
20
1
Order By: Relevance
“…When we transplanted HPAF-2 human pancreatic cancer cells in the pancreas of athymic mice, we found that liver metastasis was increased by n6PUFA-enriched diet and decreased by n3PUFAenriched diet [16]. In addition, dietary FAs also regulated liver metastasis of colorectal cancer [32,33]. In the present study, diet-derived unsaturated FAs induced an increase of the same FAs in the liver.…”
Section: Hepatic Fassupporting
confidence: 63%
“…When we transplanted HPAF-2 human pancreatic cancer cells in the pancreas of athymic mice, we found that liver metastasis was increased by n6PUFA-enriched diet and decreased by n3PUFAenriched diet [16]. In addition, dietary FAs also regulated liver metastasis of colorectal cancer [32,33]. In the present study, diet-derived unsaturated FAs induced an increase of the same FAs in the liver.…”
Section: Hepatic Fassupporting
confidence: 63%
“…We established above findings in a mouse model of obesityassociated NAFLD, 9 where exercise could replicate the known benefits of physical activity, including the ameliorations in body weight, steatosis, hyperinsulinemia, and glucose tolerance. 2 Our observations are hence based on a valid experimental set up and underscore the importance of exercise for liver health.…”
Section: Discussionmentioning
confidence: 79%
“…Six weeks of feeding a HFD designed to mimic Western diet induced obesity and NAFLD without inflammation/fibrosis in mice. 9 Mean body-and liver weight increased by 11.9 g (AE2.4) and 0.8 g (AE0.2), respectively ( Fig. 1B), accompanied by a marked elevation in hepatic lipid content (Fig.…”
Section: Exercising Benefits In a Mouse Model Of Simple Steatosismentioning
confidence: 98%
See 1 more Smart Citation
“…The postoperative rehabilitation improvement mediated by ω-3 PUFAs may be due to regulation of the arachidonic acid pathway and control of the release of prostaglandins, thromboxanes, leukotrienes and other molecules, which reduces the levels of in ammatory molecules such as IL-6, IL-8, and TNF- [35][36][37] ; regulation of sterol regulatory element binding protein (SREBP-1), protein acylation reactions and calcium ion release, which maintains cell membrane integrity, stability, and uidity, thus reducing the production and release of cytokines and ameliorating, the postoperative in ammatory response 38 ; alteration of the phospholipid composition and function of T-cell membranes, which enhances the function of antigenpresenting cells and the cytotoxicity of natural killer cells and regulates the function of dendritic cells to affect immune function 39 ; and regulation of the intestinal ora and their metabolites, such as short chain fatty acids 40 .…”
Section: Discussionmentioning
confidence: 99%